Identification of Vibrio spp. Causing Vibriosis on Litopenaeus vannamei in the Kaur Traditional Ponds - Reza Wahyuni; Iman Rusmana; Sipriyadi Sipriyadi; Aceng Ruyani; Rahmad Lingga; Risky Hadi Wibowo (Jurnal Ilmu Pertanian Indonesia, 2025)
Kaur Regency is a high-potential vannamei shrimp (Litopenaeus vannamei) aquaculture area in Bengkulu Province that frequently experiences high mortality rates due to vibriosis caused by pathogenic Vibrio spp. The high shrimp mortality rates resulting in decreased production or crop failure due to attacks or infections of vibriosis disease. Data on these Vibrio spp. in traditional Kaur ponds is required for illness prevention. To identify pathogenic Vibrio spp., this study included purposeful sampling and testing, as well as data analysis. Seven Gram-negative isolates (OALF 1, 2, 3, and 5 from shrimp organs; WALF 7, 8, and 10 from pond water) produced green/yellow colonies on TCBSA medium. Biochemical tests (Gram KOH 3%, catalase, oxidase, fermentation (O/F), TSIA, MIO, lysine decarboxylase, gelatin, Simon citrate, methyl red, urease, glucose, maltose, lactose, mannitol, and sorbitol) revealed that OALF isolates from vannamei shrimp organs have morphological and physiological similarities to the pathogenic species Vibrio parahaemolyticus, whereas WALF isolates from pond water are similar to the pathogenic species V. pluvialis. The study identified Vibrio spp. as the cause of vibriosis in L. vannamei in traditional Kaur ponds, emphasizing the need for improved water and feed management, as well as proper pond environmental practices, potentially including probiotics derived from healthy local shrimp digestive bacteria, to reduce losses in vaname aquaculture in Kaur Regency, Bengkulu. Keywords: Litopenaeus vannamei, pathogen, traditional ponds, Vibrio, vibriosis